The Darwin variant - Johnson, Kenneth, 1942- (47North, 2018)
When the icy shards of a rogue comet fall to Earth, they bring an unknown virus that accelerates evolution to extremes. Suddenly, infected plants grow stronger, choking out those uninfected. Animals turn aggressive and deadly. The eyes of loved ones go cold, and infected neighbors begin exhibiting signs of brutal domination. In a small Georgia town, fourteen-year-old Katie McLane sees her neighbors changing, one by one. Dr. Susan Perry, an epidemiologist at the Centers for Disease Control and Prevention, uncovers the frightening scope of the menace. The infected aren<U+2019>t just evolving. They<U+2019>re conspiring to alter the very nature of what it means to be human. Katie and Susan become fugitives because of what they know, encountering bitter betrayals and lethal dangers, but also loves ignited and inspiring camaraderie, as they fight to prevent a viral conspiracy from creating a terrifying brave new world.